Synthesis of diethylenetriaminepentaacetic acid conjugated inulin and utility for cellular uptake of liposomes - Essien, Herbert; Lai, J. Y; Hwang, Karl J (Journal of medicinal chemistry, 1988)
The synthesis, binding of radioactive cations, liposomal encapsulation, and biodistribution of the oxidized-inulin reaction product with ethylenediamine and diethylenetriaminepentaacetic acid (4) are described. The four-step synthesis of the inulin derivative proceeded in a good overall yield of 72%. The complex of the inulin derivative with either 67Ga3+ or 111In3+ was stable in vivo and did not readily distribute into tissues, being excreted primarily in urine after intravenous administration to mice. The liposome-entrapped inulin derivative can be loaded with radioactive heavy metal cations by mobile ionophores in high radiochemical yields of 80-91%. Following the intravenous administration of the liposomal encapsulation of the indium-111-labeled inulin derivative, the entrapped compound had a biodistribution characteristic of liposomes and allowed an estimation of the extent of the intracellular uptake of liposomes. The ability of the inulin derivative to chelate many different types of metals will allow the use of this probe for studying subtle differences in tissue distribution resulting from different drug targeting or delivery protocols in the same animal by multiple labeling techniques. Moreover, the chelate-conjugated inulin permits studies of the applications of drug delivery systems in primates or human subjects by noninvasive techniques such as gamma-scintigraphic or nuclear magnetic resonance imaging methods.